Effects of a video feedback parent training program during child welfare visitation() - Nese, Rhonda N.T. (Child Youth Serv Rev, 2016)
Behavioral parent training programs have documented efficacy for improving behaviors among parents and their children and are frequently used by child welfare agencies to prevent removal of a child from the parental home or to facilitate reunification. Although an ideal time for parent training might be during supervised visits where parents may practice skills with their children under the guidance and support of a therapist or caseworker, this is not typically the case. Most often, parents within the child welfare system receive parent training in small groups without their children present, and to date, few studies have examined effects of behavioral parent training interventions during supervised visitation. In this study, concurrent multiple baseline across behaviors design was used to examine effects of a behavioral parent training program, Filming Interactions to Nurture Development (FIND), on parental skill acquisition with four mothers who had lost custody of their children but were being considered for reunification. Children emitted little or no problem behaviors during baseline or intervention, so parenting behavior was the primary dependent variable. Results obtained across participants documented a clear functional relation between implementation of the FIND intervention and increases in developmentally supportive parenting behaviors. Results of social validity and contextual fit measures suggest the intervention was perceived by mothers to be positive, feasible, and appropriate within the child welfare context. Practical and conceptual implications, limitations of this study, and directions for future research are discussed.